Dual-responsive chondroitin sulfate self-assembling nanoparticles for combination therapy in metastatic cancer cells - Ensieh Poursani; Giuseppe Cirillo; Manuela Curcio; Orazio Vittorio; Michele De Luca; Antonella Leggio; Fiore Pasquale Nicoletta; Francesca Iemma (Elsevier, 2024)
In this study, we developed self-assembling nanoparticles (LCPs) able to trigger the release of Chlorambucil (Chl) and Doxorubicin (DOX) to MDA-MB-231 cells by exploiting the enzyme and redox signals. The DOX loaded LCPs was prepared by the self-assembly of two chondroitin sulphate (CS) derivatives, obtained by the covalent conjugation of Lipoic Acid (LA) and Chlorambucil (Chl) to the CS backbone. After the physic-chemical characterization of the conjugates by FT-IR, 1H NMR, and determination of the critical aggregation concentration, spherical nanoparticles with mean hydrodynamic diameter of 45 nm (P.D.I. 0.24) and Z-potential of - 44 mV were obtained by water addition/solvent evaporation method. In vitro experiments for the release of Chl and DOX were performed in healthy and cancer cells, using a cell culture media to maintain the physiological intracellular conditions (pH 7.4) (and concentration of esterase and GSH. The results allowed the selective release of the payloads to be detected: Chl release of 0 and 41% were obtained after 2 h incubation in normal and in cancer cells respectively, while values of 35 (in healthy cells) and 60% (in cancer cells) were recorded for DOX release after 96 h. Finally, viability studies proved the ability of the newly proposed nanosystem to enhance the cytotoxic activity of the two drugs against cancer cells.